(3efXhQ TGeds - (3UdGM eMeO(B, (3PjGHs ((3YeGf(B:s (3OGQ GdacQ(B,s, 2009)
(3eaghe h JWhQ GdGOGQI GdUMjI GdfXGe GdUMj h GdJNWjW GdUMj , GdJfXje h Gdgjcd GdJfXjej aj GdeSJTajGJ h GdeQGcR GdUMjI , EOGQI Gdbhi GdHTQjI hGdQbGHI aj GdeSJTai h GdeDSSGJ GdUMjI GdhXGFa h GdegGe ddGbSGe h GdhMOGJ GdJfXjejI I Jbjje GdGOGA aj GdeSJTajGJ , EOGQI GdUQGY aj GdeSJTais
Keywords: (3GdUMI GdYGeIs; (3GdeSJTajGJ `` GOGQIs; (3GdeTJTajGJs